A pilot mixed methods randomized control trial investigating the feasibility and acceptability of a culturally tailored intervention focused on beliefs, mistrust and race-congruent peer support for Black adults with diabetes - Wen, Meng-Jung; Maurer, Martha; Pickard, Annika L.; Hansen, Makenzie; Shiyanbola, Olayinka O. (Frontiers in Public Health, 2025)
IntroductionBlack adults disproportionately experience poor glycemic control and medication nonadherence, yet few diabetes self-management programs address their unique health beliefs, provider mistrust and sociocultural barriers to taking diabetes medications. This 6-month pilot randomized feasibility trial compared a culturally tailored diabetes self-management program, incorporating beliefs about diabetes, mistrust, and race-congruent peer support to a standard diabetes program.MethodsAn embedded mixed methods design examined the feasibility of the pilot trial, including recruitment, retention, intervention adherence and participant acceptability. Data were collected through participant self-reported questionnaires, field notes, semi-structured interviews, and focus groups. Qualitative content analysis inductively explored participants’ feedback on the program, participation barriers and potential strategies to overcome the challenges. Mixed methods integration was implemented using a side-by-side joint display to compare, synthesize and interconnect the quantitative and qualitative results across all feasibility domains.ResultsThirteen participants (93%) completed the trial, demonstrating high adherence and retention. Community outreach and a prerequisite orientation using motivational interviewing were feasible and appropriate to recruit potential participants. Participants expressed high satisfaction and acceptability, highlighting the importance of peer support, cultural relevant content and a safe space for sharing experiences. Barriers to participation were identified including schedule conflicts and difficulties in engagement.DiscussionFuture large-scale effectiveness trials should consider combining multimedia into recruitment methods, tailoring the program to address medication-taking goals, and addressing social and environmental barriers to support sustained lifestyle changes.